PHYSICS AND MATHEMATICS EDUCATION STUDENTS’ FEEDBACK: A CASE STUDY ON THE USE OF AI-CALI IN TEACHING ENGLISH FOR SCIENCE STUDENTS - Ahmed Sardi; Syarifuddin Dollah; Abdullah Abdullah (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2026)
This study examines physics and mathematics education students’ feedback on the implementation of AI enhanced Computer Assisted Language Instruction in teaching English for Sciences. As artificial intelligence becomes increasingly integrated into higher education, understanding students’ experiences in using AI supported language learning within discipline specific contexts is essential for effective pedagogical development. This study employed a qualitative descriptive design involving twenty undergraduate students consisting of ten physics education students and ten mathematics education students at STKIP DDI Pinrang. Data were collected through semi structured interviews and analyzed using thematic analysis to identify patterns in student responses. The findings indicate that students generally have positive perceptions of AI enhanced CALI in English learning. They value features such as personalized feedback, accessibility, and support for vocabulary development and basic grammar. However, several limitations were identified, particularly in the ability of AI to explain discipline specific concepts and support advanced academic writing and scientific communication. Differences in responses were also influenced by students’ levels of English proficiency and familiarity with digital technology. This study concludes that AI enhanced CALI has strong potential to improve English for Sciences instruction when supported by appropriate pedagogical strategies and human interaction. The findings contribute to the development of technology integrated ESP learning and provide insights for optimizing AI use in higher education contexts.